Documenting socialism : East German documentary cinema - Allan, Seán 1961- HerausgeberIn; Heiduschke, Sebastian 1974- HerausgeberIn (Berghahn, 2024)
More than 30 years after the collapse of the German Democratic Republic, its cinema continues to attract scholarly attention. This volume moves beyond the traditionally analyzed feature film production and places East Germany’s documentary cinema at the center of history behind the Iron Curtain. Covering questions of gender, race and sexuality and the complexities of diversity under the political and cultural environments of socialism, the specialist contributions in this volume cohere into an introductory milestone on documentary film production in the GDR.